Analisis Efektifitas Tata Kelola SDM Terhadap Peningkatan Kinerja Pegawai di Dinas Koperasi dan UKM Kota Serang 2025 - Satrio Ramadhan; Laeli Nur Khalifah; Muhammad Zaki Bagus Priantoro; M Alif Mahesa Tanujiwa; Silpius Kegiye (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the effectiveness of human resource (HR) governance in improving employee performance at the Serang City Cooperatives and SMEs Office in 2025. The research method used is a quantitative approach with a survey design, involving 100 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression to test the effect of HR governance variables, which include planning, organizing, implementing, and supervising, on employee performance. The results of the study indicate that HR governance has a positive and significant influence on improving employee performance at the Serang City Cooperatives and SMEs Office. Specifically, clear HR planning, efficient organization, structured implementation, and effective supervision have been shown to increase employee productivity and work quality. The implication of this study is the importance of improving and strengthening HR governance as a strategy to improve employee performance, which ultimately can increase productivity, efficiency, and effectiveness in carrying out the duties and responsibilities of local government agencies.